Management of Trauma in COVID-19 Patients: An Adaptation of Practice - Samuel Ern Hung, Tsan (Malaysian Society of Anaesthesiologists, 2022)
Over the past two and a half years, the world has been living in the shadow of the COVID-19 pandemic. Malaysia has been similarly affected, reporting a total of 4,575,809 cases and 35,784 deaths till 5th July 2022.1 During this time, the medical field has learned to fight this virus and its complications. Public health measures such as mass vaccinations and infection control precautions were implemented to reduce the spread of COVID-19. Despite this, the COVID-19 virus continued to evolve, with no clear end in sight until today. Therefore, healthcare practitioners must remain constantly vigilant in the management of COVID-19 patients, regardless of whether infection rates spike or wane. This review aims to demonstrate the principles of management of COVID-19 patients presenting with trauma.